Power Dynamics in Adolescent Couple Relationships and Risk of Sexually Transmitted Infections and HIV - T.R. Sanchez, Maria; Bermudez, Maripaz; Buela-Casal, Gualberto (Current HIV Research, 2013)
The aim of this study was to determine whether there are differences in power distribution between males and females in couple relationships, and whether these differences are associated with risky sexual behaviour in a representative sample of Spanish adolescents. The study also examined the influence of partner's age on the power dynamics that occur in a relationship. The sample comprised 1,223 adolescents attending state and private schools in the 17 autonomous regions in Spain. All adolescents included in the sample were involved in a heterosexual relationship (for at least one month) at the time of evaluation. Relationship control and decision-making dominance were evaluated using the Spanish version of the Sexual Relationship Power Scale. Two further questionnaires were administered to collect sociodemographic data, and data on sexual behaviour. Females showed greater relationship control and greater control over decision-making than males. In the female group, participants with partners five or more years older than them were found to have less control over decision-making, while greater control over decision-making was linked to less exposure to risk. In the male group, participants with partners older than them were found to have greater control over decisionmaking, while relationship control was found to be negatively related to exposure to sexual risk. These results highlight the importance of taking power distribution and gender inequalities in couple relationships into consideration for STI and HIV prevention.
Keywords: gender inequality